Profile of Maternal Mortality due to Cardiovascular Disease Based on Determinant Factors at Dr. Soetomo Regional General Hospital - Akhmad Adam Mahendra; Andrianto; Muhammad Ardian Cahya Laksana (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Background: Although Indonesia’s maternal mortality rate (MMR) decreased from 346 per 100,000 live births in 2010 to 189 in 2020, it remains high compared to other Southeast Asian countries. Cardiovascular diseases are among the leading indirect causes of maternal deaths globally, accounting for over 33% of cases. Objectives: This study aims to analyze maternal mortality due to cardiovascular disease at Dr. Soetomo Regional General Hospital based on determinant factors. Methods: This study was a descriptive analytical study utilized secondary data from medical records of 123 patients who experienced maternal deaths due to cardiovascular disease at Dr. Soetomo Hospital between January 2020 and December 2023. Determinants were categorized as near (cardiovascular diagnosis), intermediate (maternal age, gestational age, obstetric status, and delivery mode), and distant (occupation) factors. Results: Of 123 cases, the leading cardiovascular complications were hypertension in pregnancy (58.5%), congenital heart disease and pulmonary hypertension (15.4%), and cardiomyopathy and  heart failure (14.6%). Intermediate determinants included maternal age >35 years (28.5%), multigravida status (60.2%), multiparity (56.9%), and third-trimester presentation (65%). Most deaths (96.7%) occurred postpartum, with cesarean section being the predominant delivery mode (74.8%). The majority of patients were housewives (53.7%). Conclusion: Hypertension in pregnancy remains a primary near determinant of maternal mortality. Intermediate and distant determinants, such as maternal age, obstetric status, and socioeconomic factors, also contribute significantly. Efforts to reduce maternal mortality should include improved antenatal care, early cardiovascular screening, and targeted public health interventions. - Highlights: 1. This study reinforces hypertension in pregnancy (58.5%) as the leading cause of maternal mortality due to cardiovascular disease, highlighting its significant contribution compared to other conditions like congenital heart disease (15.4%) and cardiomyopathy (14.6%). 2. A striking 96.7% of maternal deaths occurred postpartum, with cesarean section (74.8%) being the predominant delivery mode, suggesting a need for enhanced postpartum monitoring and cardiovascular care in high-risk pregnancies.